Effective Strategy in Teaching English Speaking - Anggraini, Nabilla; Santoso, Didiek (Yayasan Daarul Huda Kruengmane, 2024)
One of the important aspects that need to be considered in the process of instruction is teaching strategies. Hence determining appropriate teaching strategies can improve learning outcomes well. The objective of this research is to know and to describe the strategies of teaching English speaking. It was conducted at Budisatrya Junior High School Medan and used qualitative descriptive method. The data was collected through interview, questionnaire, observation, and documentation. The research found that the teaching English speaking strategies used by the school have been widely influence by communication and students-center strategies. This measure taken has given much beneficial impact to all parties, particularly teachers and students for their English speaking development. Therefore, in teaching speaking, it is important for everyone, particularly educator to develop their teaching strategies which meets to the students need.